2022
DOI: 10.1297/cpe.2021-0032
|View full text |Cite
|
Sign up to set email alerts
|

Oral disintegrating desmopressin tablet is effective for partial congenital nephrogenic diabetes insipidus with <i>AVPR2</i> mutation: a case report

Abstract: Copyright© 2022 by The Japanese Society for Pediatric Endocrinology Highlights• Oral disintegrating DDAVP can be effective and safe in patients with partial congenital NDI due to AVPR2 gene mutations.• Treatment with 720 µg of DDAVP per day reduced our patient's urine output by approximately 30%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
(31 reference statements)
0
0
0
Order By: Relevance
“…DDAVP does not inherently address the pathogenesis of NDI. However, contrary to expectations, several reports have suggested that DDAVP can be effective in specific cases of NDI (16)(17)(18)(19)(20)(21)(22)(23)(24). Fujimoto et al documented that 21.7% of patients with NDI received DDAVP, with a response rate of 33.3% for acquired NDI (16).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…DDAVP does not inherently address the pathogenesis of NDI. However, contrary to expectations, several reports have suggested that DDAVP can be effective in specific cases of NDI (16)(17)(18)(19)(20)(21)(22)(23)(24). Fujimoto et al documented that 21.7% of patients with NDI received DDAVP, with a response rate of 33.3% for acquired NDI (16).…”
Section: Discussionmentioning
confidence: 93%
“…However, how often DDAVP reduces the urine output in lithium-induced NDI is unclear. Nevertheless, reports have indicated the efficacy of high doses of DDAVP in the treatment of NDI (17)(18)(19)(20)(21)(22)(23)(24). Among these reports, only four cases of lithium-induced NDI in response to DDAVP have been documented (Table 4).…”
Section: Discussionmentioning
confidence: 99%